2014
DOI: 10.3892/ijo.2014.2567
|View full text |Cite
|
Sign up to set email alerts
|

Evolving therapeutic concepts in prostate cancer based on genome-wide analyses (Review)

Abstract: Treatment of castration resistant prostate cancer (CRPC) continues to represent a major urooncological challenge due to tumor heterogeneity and the inevitable development of therapy resistance. Although androgen deprivation therapy retains an important role in the management of CRPC, recent evidence suggests that a broader spectrum of therapeutic targets may improve patient response and delay development of advanced disease. Genome-wide analyses have identified four major signaling nodes that are most frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 70 publications
(78 reference statements)
1
13
0
Order By: Relevance
“…4A). MEK-ERK pathway and PI3K-AKT impact multiple aspects of prostate cancer biology (25). PF-03084014 impaired MEK and ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…4A). MEK-ERK pathway and PI3K-AKT impact multiple aspects of prostate cancer biology (25). PF-03084014 impaired MEK and ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies demonstrated that the increasing effect of EGFR on COX‐2 expression was mediated by kinases PI3K and MSK‐1 (the latter previously activated by MAP kinases p38 and Erk1/2). Interestingly, most of the components of the pathway leading to COX‐2 upregulation, such are c‐Src, EGFR, PI3k‐Akt, and Erk1/2, have been suggested to play relevant roles in PC, as indicated in several review articles (Georgi et al, ; Guérin, Fischel, Ferrero, Bozec, & Milano, ; Toren & Zoubeidi, ; Vlaeminck‐Guillem, Gillet, & Rimokh, ). Consequently, the positive feedback loop of COX‐2 upregulation triggered by iPGE 2 might also contribute to maintain a constant stimulation on these kinases involved in the progression of PC.…”
Section: Discussionmentioning
confidence: 99%
“…HH and MEK1/2-ERK1/2 pathways are both involved in prostate cancer [43,44,124]. EGF signaling has been shown to increase the invasive capability of ARCaP E human prostate cancer cells via upregulation of pERK1/2 and of GLI1.…”
Section: Prostate Cancermentioning
confidence: 98%